Work effort, moderation in expulsion and illegal migration - Oded Stark (University of Warsaw, Centre of Migration Research (CMR), 2006)
Illegal migrants supply a valuable productive input: effort. But their status as illegals means that these migrants face a strictly positive probability of expulsion. A return to their country of origin entails reduced earnings when the wage at origin is lower than the wage at destination. This prospect induces illegal migrants to exert more work effort than comparable workers who face no such prospect. The lower the probable, alternative earnings, the harsher the penalty that illegal migrants will be subjected to upon their return, for a given probability of expulsion, and the higher the level of effort they will exert at destination. While the homecountry wage that awaits the illegal migrants upon their return is exogenous to the host country, the probability of their return is not. Given the home-country wage, a higher probability of expulsion will induce illegal migrants to supply more effort. Hence, different combinations of probabilities of expulsion and home-country wages yield the same level of effort. Thus, variation in the extent to which receiving countries undertake measures aimed at apprehending and expelling illegal migrants can be attributed not to characteristics of the illegal migrants themselves but to a feature that pertains to the illegal migrants' country of origin.
Keywords: D72; F22; J61; K42; O15; 330; Illegal migration; Probability of expulsion; Home-country wage; Work effort; Moderation in expulsion; Illegale Migration; Arbeitsangebot; Lohn; Theorie